Habitat suitability modeling to improve conservation strategy of two highly-grazed endemic plant species in saint Catherine Protectorate, Egypt - Mohamed M. El-Khalafy; Eman T. El-Kenany; Alshymaa Z. Al-Mokadem; Salma K. Shaltout; Ahmed R. Mahmoud (BMC Plant Biology)
Abstract Background Biodiversity is seriously threatened by climate change impacts in the long term. Conservationists must possess a comprehensive knowledge about habitat suitability of different species and factors that control their distribution in order to effectively minimize biodiversity loss. Results The present study showed the response of two endemic taxa in Saint Catherine protectorate (SKP) (Micromeria serbaliana and Bufonia multiceps) to anticipate climate change over the next few decades using species distribution models. In our analysis, we included the incorporation of bioclimatic variables into the SDM modeling process using four main algorithms: generalized linear model (GLM), Random Forest (RF), Boosted Regression Trees (BRT), and Support Vector Machines (SVM) in an ensemble model. The RF model outperformed other models when analyzing Micromeria serbaliana, whereas BRT demonstrated superiority in the case of Bufonia multiceps. The ensemble models exhibited the best performance, achieving a mean TSS of 0.94 for Micromeria serbaliana and 0.86 for Bufonia multiceps. Micromeria serbaliana was mainly affected by Mean temperature of wettest quarter (Bio8), elevation, and Aridity index. On the other hand, the most significant factors influencing Bufonia multiceps were determined to be Isothermality (Bio2/Bio7) × 100 (Bio3), and elevation. The habitat suitability of Micromeria serbaliana was slightly expanded during the period form 2041–2060, then declined again from 2061 to 2080, while it showed moderate expansion in the case Bufonia multiceps under the two periods. Conclusion The results of our research support the urgent need for conservation efforts, including reintroduction and planning for in situ and ex situ conservation in appropriate habitats. Clinical trial number Not applicable.